A survey study of the opinions of a sample of teaching and administrative staff in Zakho University, Kurdistan Region, Iraq - Sami, Viyan M.; Elias, Saad Kh.; Jameel, Farhad S. (Humanities Journal of University of Zakho, 2024)
This study investigates the impact of self-leadership on the adoption of green university practices at the University of Zakho. Self-leadership is conceptualized as a multidimensional construct encompassing focus on behavior, natural reward, and constructive thinking. The researchers used a random sampling method to distribute 103 questionnaires to teaching and administrative staff members at the University of Zakho. 95 questionnaires were returned, and 76 were deemed valid for statistical analysis. The researchers used a descriptive approach to collect and analyze the data using the AMOS 26 program. The study found that there is a positive correlation between self-leadership and green university practices. The study also found that the dimensions of self-leadership (focus on behavior, natural reward, and constructive thinking) are significant predictors of green university practices. The study concludes that the interest of teaching and administrative staff members in self-leadership is an indicator of the progress of the University of Zakho in terms of green university practices. The study also recommends that the university continue to emphasize the importance of self-leadership in order to promote environmental sustainability on campus.